An aqueous extract of trunk bark of Ficus religiosa has anxiolytic activity - Ratnasooriya, W.D; Jayakody, J .R . A .C .; Dharmasiri, M . G . (My University, 1998)
The aim of this study was to evaluate the anxiolytic potential of a water extract of trunk bark of Ficus religiosa. This was tested in rats using the Vogel conflict test .system. I ml o f different concentrations of the extract (12.5, 25, 125, 250, 500 mg/kg) or water (vehicle) was orally administered (three times per day) to different groups of rats and the average number of mild electrical shocks accepted per minute was determined as a measure of anxiolysis. The results showed a potent anxiolytic activity with a rapid onset- The anxiolytic activity was, however, not doserelated. The effect was also not accompanied by sedation (measured in terms of number of head dips, time per head dip, number of rear or locomotory activity in rat hole-board technique) or loss of motor coordination due to muscle relaxation (in terms of time for righting reflex). Further, the extract was non-toxic (in terms of haematology. rectal temperature, body weight and food and water intake) even when given three times a day for seven consecutive days. Overall, the results suggest that the anxiolytic effect is unlikely to have been mediated via a gamma-aminobutyric acid mechanism as with benzodiazepines. We conclude that it may be possible to isolate from this plant promising anxiolytic agents or develop lead compounds without undesirable sideeffects